A comparison of three-point shooting effectiveness in the Euroleague and NCAA DI basketball - Karamousalidis, G.; Foteinakis, P.; Konstantinidis, G.; Kifonidis, D.; Kourtis-Doulkeridis, A.; Symeonidou, S. (Journal of Human Sport & Exercise, 2025)
Shooting is a fundamental basketball skill that critically influences game outcomes. The purpose of the present study was to compare the effectiveness of three-point shooting between the Euroleague and NCAA Division I during the 2020-21 season, evaluating factors such as shooting accuracy, player position, type of offense, and timing of shot execution. The analysis was based on the recording of 3,249 shots from 70 games. Results demonstrated higher shooting percentages in the Euroleague (38.4%) compared to the NCAA (35.1%). Differences were observed in the type of offense, with the NCAA exhibiting a higher proportion of fast-break (transition) plays, whereas the Euroleague primarily focuses on organized set plays. Shot execution timing emerged as the most significant differentiating factor between the two leagues. Player position also influenced effectiveness, with guards being the primary shooters, however, forwards in the Euroleague demonstrated higher efficiency compared to their NCAA counterparts. CHAID analysis confirmed the importance of shot timing, player position, and shooting effectiveness as critical discriminant factors, highlighting the Euroleague`s tendency towards more patient and tactically organized offenses in contrast to the faster and more intense style of play in the NCAA. These findings provide valuable insights for analysts and coaches to develop effective offensive tactics tailored to the specific characteristics of each competition.